(3eY GdETGQI Edi MGdI GdLRGFQs - (3fajSI(B, (3fGUQjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3JfGhd GdcGJH GdESJKeGQ GdCLfHj GdeHGTQ hJehjd GdJfejI GdGbJUGOjI HGdHdOGf GdfGejI, MjK JMOK ef NdGd aUhd OQGSJg Yf GdGWGQ GdfXQj ddJfejI GdGbJUGOjI h Jehjd GdJfejI GdGbJUGOjI, HGdGVGaI Gdi GdGWGQ GdfXQj ddGSJKeGQ GdCLfHj GdeHGTQ hfXQjGJg, hGdGJaGbjGJ GdOhdjI hhGbY GdGSJKeGQ GdCLfHj GdeHGTQ aj GdLRGFQ eY Jbjje efGNg(B. s
(3GdeQGLY U(B.419s
Keywords: (3GdGSJKeGQGJ GdCLfHjI (B- (3GdLRGFQs